Analisis Peran Agama Islam Dalam Menanggulangi Penyalahgunaan Narkoba di Kalangan Remaja - Siregar, Hapni Laila; Yulinda, Anggi; Fadhilah, Arisyah Dwi; Mawaddah, Uly Anti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Drug abuse among teenagers is a critical issue that threatens the health and future of the younger generation. This research examines the role of Islam in preventing and treating drug abuse among teenagers. The methodology used is a quantitative approach by collecting data through distributing questionnaires. The research results show that Islamic values and teachings have a significant influence in shaping positive behavior and avoiding drug abuse. Religious education in families, schools and communities plays an important role in building awareness and understanding among teenagers about the dangers of drugs. In addition, spiritual and social support from the Muslim community helps teenagers deal with the social and emotional pressures that often trigger drug abuse. This research recommends strengthening religious education programs and increasing the role of mosques and Islamic organizations in anti-drug campaigns to create a conducive environment for the development of healthy and drug-free youth.